The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/annrheumdis-2021-eular.871
|View full text |Cite
|
Sign up to set email alerts
|

Op0099 epidemiology and Mortality of Ra-Associated Interstitial Lung Disease: Data From a French Administrative Healthcare Database

Abstract: Background:Interstitial lung disease (ILD) is a common extra-articular manifestation of RA and is associated with increased morbidity and mortality.1-3 Studies have shown variability in the prevalence and mortality rate of patients with RA-associated ILD (RA-ILD).4 Further studies are needed to better characterise the epidemiology of RA-ILD.Objectives:To estimate the prevalence and incidence of clinical RA-ILD in France and to compare mortality rates between patients with RA-ILD and patients with RA without cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study aimed to estimate the prevalence and incidence of clinical interstitial lung disease (ILD) complicating RA in France and to compare mortality rates between patients with RA-ILD and patients with RA without clinical ILD (RA-noILD) [20]. This study revealed that the prevalence of RA-ILD was 6.52 per 100,000 inhabitants, corresponding to an incidence of 1.04 per 100,000 PY, and the mortality rate was 1.71 per 100,000 inhabitants.…”
Section: Assessment Of Disease Burdenmentioning
confidence: 99%
“…A study aimed to estimate the prevalence and incidence of clinical interstitial lung disease (ILD) complicating RA in France and to compare mortality rates between patients with RA-ILD and patients with RA without clinical ILD (RA-noILD) [20]. This study revealed that the prevalence of RA-ILD was 6.52 per 100,000 inhabitants, corresponding to an incidence of 1.04 per 100,000 PY, and the mortality rate was 1.71 per 100,000 inhabitants.…”
Section: Assessment Of Disease Burdenmentioning
confidence: 99%
“…
Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) has garnered increasing attention because of reports of higher-than-expected prevalence with persistent excess mortality, despite the availability of antifibrotics as novel therapeutic options. [1][2][3][4] Although antifibrotics have only modest efficacy, emerging therapeutic options have bolstered efforts for risk stratification, early detection, and identifying risk factors for progression of RA-ILD. Chest high-resolution computed tomography (HRCT) scan is the gold standard for ILD diagnosis.
…”
mentioning
confidence: 99%